Chapter Aesthetics and politics in contemporary South Africa - Shefer, Tamara (Amsterdam University Press, 2023)
South Africa is a context within which Rosemarie Buikema has thought deeply and conducted much of her empirical research for her book Revolts in Critique. This contribution pursues some of the ways in which Buikema's scholarship resonates with contemporary South African currents of thinking towards justice goals, within the academy and in the larger post-apartheid South Africa. Buikema's work provides a valuable philosophical framework for thinking with art for change, particularly through her feminist postcolonial conceptualization of the 'poetics of recycling' which underlines the assertion that the articulation and/or the memory of trauma is not a linear process but a cycle that has to be reiterated, time and again in order to open up alternative imaginaries. I explore in particular the productive possibilities of this framework in thinking with current South African feminist decolonial and queer scholarship, art and activism that deploys imagination and creativity to disrupt the raced, classed, and gendered inequalities and violences that still characterise this local landscape.